Pemanfaatan Media Pembelajaran Blog dalam Meningkatkan Kemampuan Menulis Feature Mahasiswa - Nufus, Hayatun; Subyantoro, Subyantoro; Pristiwati, Rahayu (LPPM Universitas PGRI Silampari Lubuklinggau, 2022)
Learning media are all things that can be used in conveying information in the learning process so that the material can be received and can foster interest in learning in students in learning. For this reason, this study aims to describe the use of instructional media, especially blogs, in improving students' feature writing skills. The method used in this study is a mixed method. This research was conducted at PGRI Palembang University. Data collection techniques were carried out by interviews and feature writing performance tests. Based on the results of the study, it was shown that students used their mobile phones to use blogs and the constraints in using blogs were that students were embarrassed to publish their writings and opening blogs required an internet network. Then, from the results of the analysis of feature written documents published on blogs, it shows that students' ability to write features in utilizing blogs is 35 students getting very good grades, 25 students getting good grades, and 8 students getting fair grades.